The bad seed - John, Jory; Oswald, Pete (New York Harper, an imprint of HarperCollins Publishers, 2017)
A naughty seed with a bad attitude, bad temper, and bad manners vows to change his life for the better, but his efforts are met with skepticism by his friends.
ALA Booklist
Kirkus Reviews
Publishers Weekly
AD 390
2.0
1-4
Keywords: Behavior -- Juvenile fiction; Conduct of life -- Juvenile fiction; Life change events -- Juvenile fiction; Behavior -- Fiction; Conduct of life -- Fiction; Life change events -- Fiction; Human behavior -- Fiction; Conduct of life -- Fiction; Life change events -- Fiction